Injury profiles and clinical management of older patients with major trauma. (5th October 2021) - Ferrah, Noha; Dipnall, Joanna; Gabbe, Belinda; Cameron, Peter; Ibrahim, Joseph; Beck, Ben
Abstract: Objectives: This study aimed to characterise the most common injury profiles and interventions in older major trauma patients, and how they change with age. Methods: This is a retrospective review of interventions, injury profiles and outcomes of major trauma patients aged 65 years and older from 2007 to 2018, using data from the Victorian State Trauma Registry. A latent class analysis (LCA) was used to identify homogenous injury groups. Results: The LCA identified five injury profiles: isolated head injury; chest/upper limb injuries; multi‐trauma; isolated spine; and head/chest/upper limb. Among 10, 001 patients, 50% had an isolated head injury, and 83% of patients received definitive treatment at a major trauma centre. 50% of patients received a surgical or non‐surgical intervention, and 36% underwent surgery. These proportions declined with increasing age. Conclusions: Older patients with major trauma are a heterogeneous group, whose mechanisms and patterns of injury, and clinical management change with increasing age.